Perbankan Syariah di Indonesia - Julika, Leny; Andrini, Rozi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Islamic banking industry in Indonesia has grown rapidly over the past two decades, driven by increasing demand from the Muslim community for Sharia-compliant financial services, as well as supportive government policies. This article aims to analyze the development, challenges, and prospects of the Islamic banking industry in Indonesia in 2023 and 2024, using a descriptive qualitative approach with secondary data analysis. The results show that, although Islamic banking has achieved significant growth in terms of assets and customer base, challenges related to regulation, public literacy, and competition with conventional banks remain key obstacles. This study is expected to enhance understanding of the Islamic banking landscape in Indonesia and provide strategic recommendations for strengthening this industry in the future.